2021
DOI: 10.1111/1754-9485.13184
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy in the management of hepatocellular carcinoma: An Australian multi‐institutional patterns of practice review

Abstract: IntroductionStereotactic body radiotherapy (SBRT) is an emerging, therapeutic option in the management of hepatocellular carcinoma (HCC). A multicentre Liver Ablative Stereotactic Radiation (LASR) database was established to provide a collaborative platform for Australian institutions to define the practice of liver SBRT for HCC. This study explores the patterns of SBRT practice amongst Australian institutions.MethodsThis was a multi‐institutional retrospective study of patients treated with SBRT for HCC at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In Australia, we have observed an increased utilisation of SBRT in the management of HCC including as a first‐line, curative intent treatment. 9 An Australia multi‐centre retrospective review reported outcomes following curative intent SBRT in 68 patients with treatment naïve BCLC early‐stage, solitary HCC up to 5 cm with compensated CP A cirrhosis. 18 The two‐year freedom from local progression was 94%, PFS was 60% and OS was 88%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, we have observed an increased utilisation of SBRT in the management of HCC including as a first‐line, curative intent treatment. 9 An Australia multi‐centre retrospective review reported outcomes following curative intent SBRT in 68 patients with treatment naïve BCLC early‐stage, solitary HCC up to 5 cm with compensated CP A cirrhosis. 18 The two‐year freedom from local progression was 94%, PFS was 60% and OS was 88%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews of SBRT in early‐stage HCC have demonstrated 3‐year local control rates of 93% 8 . Utilisation of SBRT in HCC has also increased worldwide, with application in a range of disease stages 9 . However, there is limited data on survival outcomes following SBRT in the management of treatment naïve, early‐stage and solitary HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Liver function is currently assessed via scoring systems such as the Child-Pugh (CP), Albumin-Bilirubin (ALBI) and Model for End-stage Liver Disease (MELD) scores, all of which are based on biochemical markers indirectly linked to liver function [ 8 , 9 ]. Liver SBRT dose prescriptions for HCC are commonly based on the CP scoring system [ 10 ]. CP scores can range from 5 to 15 and are classified as CP-A (5–6 points, well-compensated cirrhosis), CP-B (7–9 points, cirrhosis with significant liver function compromise) and CP-C (10–15 points, decompensated cirrhosis).…”
Section: Liver Function Assessmentmentioning
confidence: 99%
“…The uptake of this treatment technique worldwide has been rapid, 2 particularly for lung, 3 spine 4 and liver treatments 5 . In Australia and New Zealand, SABR is available in all states, major cities and some rural centres.…”
Section: Introductionmentioning
confidence: 99%